Antioxidant and Antimicrobial Activities of Methanolic Extract from Jatropha curcas Linn. Fruit - Saosoong, a; Ruangviriyachai*, Chalerm (Asian Journal of Chemistry, 2014)
The present study was designed to evaluate the antioxidant activity and also antimicrobial activity with total phenolic content of the crude methanolic extract from J. curcas Linn. fruit. The dried samples were extracted by 60 % (v/v) methanol to obtain the crude methanolic extract. The total phenolic content of the crude methanolic extract which was analyzed by Folin-Ciocalteu method was 7.04 ± 0.10 mg/g as GAE. The evaluation of antioxidant activity of the crude methanolic extract was performed by using two methods including 2,2-diphenyl-1-picryhydrazyl and Phen assay. The results showed that the antioxidant activity of this extract was 270.98 ± 0.59 μmol Fe/g of extract for Phen assay and the extract gave IC50 at 14.09 ± 0.05 mg/mL for 2,2-diphenyl-1-picryhydrazyl assay. Additionally, as the antimicrobial activity evaluation, this extract exhibited the potencies of antimicrobial activity against P. putida, P. syringae pv. sesami, X. campestris, X. campestris pv. glycines, X. campestris pv. vesicatoria and R. solanacearum with the presence of inhibition zone in the range of 8.0 ± 0.0 to 13.7 ± 0.6 mm and MIC value at 214.29 ± 0.00 μg/mL. All test methods showed that the crude methanolic extract from J. curcas Linn. fruit had a higher total phenolic content and antioxidant activity than J. curcas seed oil in previous work, while the antimicrobial activity was moderated. Therefore, these results suggested that J. curcas Linn. fruit has highly potential as effective natural bioactive sources.